Understanding Parkinson Disease: A Complex and Multifaceted Illness. Issue 6 (December 2015) - Gopalakrishna, Apoorva; Alexander, Sheila A.
Abstract : ABSTRACT: Parkinson disease is an incredibly complex and multifaceted illness affecting millions of people in the United States. Parkinson disease is characterized by progressive dopaminergic neuronal dysfunction and loss, leading to debilitating motor, cognitive, and behavioral symptoms. Parkinson disease is an enigmatic illness that is still extensively researched today to search for a better understanding of the disease, develop therapeutic interventions to halt or slow progression of the disease, and optimize patient outcomes. This article aims to examine in detail the normal function of the basal ganglia and dopaminergic neurons in the central nervous system, the etiology and pathophysiology of Parkinson disease, related signs and symptoms, current treatment, and finally, the profound impact of understanding the disease on nursing care.